Isolation, identification, and bioactivity of microbial metabolites of cyclopamine and its congeners. (June 2015) - Liu, Qing-xin; Yuan, Xing; Ye, Ji; Yue, Rong-cai; Shen, Yun-heng; Shan, Lei; Li, Hui-liang; Zhang, Wei-dong
Graphical abstract: The biotransformation of cyclopamine (1 ) and its congeners (2, 3 and 4 ) by Cunninghamella echinulata (ACCC 30369) was investigated. The chemical structures of two new congeners (2 and 4 ) and nine new metabolites were elucidated by NMR, HRESIMS and X-ray diffraction studies. Moreover, the relevant biological activities and the acid stabilities were also reported. Highlights: Transformation of cyclopamine (1 ) and its congeners (2, 3 and 4 ) by C. echinulata . The structures of nine compounds were confirmed by X-ray analysis. 2 and 4 showed moderate cytotoxicity in HepG2 cells and A549 cells respectively. The cytotoxicity of the nine metabolites was sharply reduced. Compound 4 induced a cyclopia phenotype in zebrafish embryos at 20 μM. Compound 4 was more stable than cyclopamine (1 ) in an acidic environment. Abstract: The biotransformation of cyclopamine (1 ) and its congeners (2, 3 and 4 ) by Cunninghamella echinulata (ACCC 30369) was investigated. The chemical structures of two new congeners (2 and 4 ) and nine new metabolites were elucidated by 1D NMR ( 1 H, 13 C and DEPT), 2D NMR (COSY, HMBC, HSQC and NOESY) and HRESIMS analyses and further confirmed by X-ray diffraction studies. Among these compounds, 2 and 4 showed moderate cytotoxicity in HepG2 cells (2, IC50 = 8.03 ± 1.92 μM) and A549 cells (4, IC50 = 10.19 ± 2.18 μM). Conversely, the cytotoxicity of the nine metabolites was sharply reduced. Similar to 1, compound 4 induced a cyclopia phenotype in zebrafish embryos at 20 μM. Moreover, compound 4 was more stable than 1 in an acidic environment.